2017
DOI: 10.1055/s-0042-121611
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic-Outlet-Syndrom

Abstract: Thoracic outlet syndrome (TOS) is one of the most extensively discussed diagnoses. There is neither a clear and homogenous clinical presentation nor an accepted definition. The term describes a complex of symptoms and complaints caused by the compression of nerves and vascular structures at one of the three defined constrictions of the upper thoracic aperture. Based on a comprehensive literature review, this article presents the etiology, epidemiology and clinical diagnostics as well as the possibilities and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Therefore many surgical approaches for removing the first rib, especially complete or partial removal of the first rib became popular ( 32 , 33 ). TFRR achieved good results (48%), but the recurrence was still high (60%−70%) and often caused damage to the vessel and brachial plexus ( 34 ). Some studies showed that the NTOS was more likely to be related to the entrapment of the scalene muscles and bands on the brachial plexus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore many surgical approaches for removing the first rib, especially complete or partial removal of the first rib became popular ( 32 , 33 ). TFRR achieved good results (48%), but the recurrence was still high (60%−70%) and often caused damage to the vessel and brachial plexus ( 34 ). Some studies showed that the NTOS was more likely to be related to the entrapment of the scalene muscles and bands on the brachial plexus.…”
Section: Discussionmentioning
confidence: 99%
“…To diagnose cervical ribs and anomalous first ribs one may use x-rays of the cervical spine and shoulder girdle and also CT, MR and electromyography. Patients present symptoms of venous obstruction, arterial insufficiency, paresthesia and pain [7,[10][11][12][13]. The therapy is often conservative, including exercises and physical therapy.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, it became more and more evident that they might cause symptoms of thoracic outlet syndrome (TOS) (Besana‐Ciani & Greenall, 2005 ; Clarys et al., 1996 ; Georgiev et al., 2007 ; Hafner et al., 2010 ; Magee et al., 2012 ). TOS is characterized by paraesthesia, compressional pain, muscle weakness, oedema and thrombosis in the distal upper limbs (DiLosa & Humphries, 2021 ; Illig et al., 2021 ; Seifert et al., 2017 ; Stewman et al., 2014 ), and might be caused by compression of nerves and blood and lymph vessels (Besana‐Ciani & Greenall, 2005 ; Boontje, 1979 ; Mérida‐Velasco et al., 2003 ; Sachatello, 1977 ; Telisky & Olinger, 2011 ). The highest compressional intensity of axillary arches is supposed to occur in abducted and externally rotated arms.…”
Section: Introductionmentioning
confidence: 99%